Manajemen Perioperatif Seksio Sesarea Pasien G2P1A0 Hamil 38 Minggu dengan Plasenta Akreta dan Plasenta Previa Totalis - Fajar A, Ratih Kumala; Jufan, Akhmad Yun; Kuncoro, Kusuma Edhi (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2019)
Placenta accreta is becoming more common and is the most frequent indication for peripartum hysterectomy. Management of cesarean delivery in the setting of a morbidly adherent placenta has potential for massive hemorrhage, coagulopathies, and other morbidities. Anesthetic management of placenta accreta presents many challenges including optimizing surgical conditions, providing a safe maternal delivery, preparing for massive hemorrhage and transfusion, preventing coagulopathies, and optimizing postoperative pain control. Balancing these challenging goals requires meticulous preparation with a thorough preoperative evaluation of the parturient and a well-coordinated multidisciplinary approach in order to optimize outcomes for the mother and fetus.